Synthesis of PANI/hematite/PB hybrid nanocomposites and fabrication as screen printed paper based sensors for cholesterol detection - Maluin, F.N.; Mohamad, S.; Rattanarat, P.; Siangproh, W.; Chailapakul, O.; Issam, A.M.; Manan, N.S.A. (Royal Society of Chemistry, 2016)
In this work, the composites of polyaniline/nano-hematite (α-Fe2O3)/Prussian Blue (PB) were successfully synthesized via a sonochemical method. This nanocomposite (PB/CPANI) has been used for the modification of paper-based sensors for cholesterol detection. The electrochemical studies of this nanocomposite showed a well-defined cyclic voltammogram for hydrogen peroxide (H2O2) with a remarkable electrochemical sensitivity. This nanocomposite modified paper-based electrode also showed excellent electrocatalytic activity towards H2O2 in the interference-free cathodic region. In addition, cholesterol oxidase was immobilized on the PB/CPANI-modified paper-based electrode for selective detection of cholesterol. Under optimum conditions, a linear range of 0.6–6.0 mM with a very low detection limit of 0.52 mM for cholesterol and a good sensitivity of 411.7 μA mM−1 cm−2 were obtained which indicated that the method presented is outstandingly appropriate to determine cholesterol in bovine serum albumin. This work might be an alternative, interference-free, and cost-effective approach for biomonitoring of cholesterol both in methodological studies and in clinical laboratories.